2021
DOI: 10.3892/mmr.2021.12145
|View full text |Cite|
|
Sign up to set email alerts
|

Regulation and mechanism of YAP/TAZ in the mechanical microenvironment of stem cells (Review)

Abstract: Stem cells receive cues from their physical and mechanical microenvironment via mechanosensing and mechanotransduction. These cues affect proliferation, self-renewal and differentiation into specific cell fates. A growing body of evidence suggests that yes-associated protein (YAP) and transcriptional coactivator with PDZ-binding motif (TAZ) mechanotransduction is key for driving stem cell behavior and regeneration via the Hippo and other signaling pathways. YAP/TAZ receive a range of physical cues, including e… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
24
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 23 publications
(24 citation statements)
references
References 129 publications
(169 reference statements)
0
24
0
Order By: Relevance
“…The upstream regulators of YAP related to mechanical forces in PSCs, including substrate stiffness [ 105 ] and surface topography [ 106 ], have been studied recently. The role of mechanical forces in embryogenesis, ECM, and topology (surface) design to support human ESC self-renewal and pluripotency has been demonstrated [ 107 , 108 , 109 ]. It has been shown that the stiffness of the coating material modulates YAP activity in PSCs.…”
Section: Yap Regulates the Self-renewal Pluripotency And Differentiat...mentioning
confidence: 99%
“…The upstream regulators of YAP related to mechanical forces in PSCs, including substrate stiffness [ 105 ] and surface topography [ 106 ], have been studied recently. The role of mechanical forces in embryogenesis, ECM, and topology (surface) design to support human ESC self-renewal and pluripotency has been demonstrated [ 107 , 108 , 109 ]. It has been shown that the stiffness of the coating material modulates YAP activity in PSCs.…”
Section: Yap Regulates the Self-renewal Pluripotency And Differentiat...mentioning
confidence: 99%
“…The activation of ciliary signalling in mesenchyme during the development of tubular organs generates mechanical forces that also activate the Hippo pathway via Yes-associated protein (YAP, also called YAP1) and its related co-transcriptional factor TAZ, which promotes cell proliferation and inhibits apoptosis [ 211 ]. It has been shown that YAP restricts the Hh-dependent differentiation of smooth muscle [ 212 , 213 ]. This indicates the important role of primary cilia as mechanical responders and Hh signal transducers to regulate cellular adaptation to mechanical loadings.…”
Section: Mechanical Regulation Of the Hedgehog Signalling Pathwaymentioning
confidence: 99%
“…but also an essential regulator of cell response to these stimuli 46 .YAP/TAZ translates a series of signals from splicing pressure to cell morphology and extracellular matrix hardness and converts them into cell-specific transcriptional programs. This mechanism of transduction is essential to drive stem cell behavior and regeneration 47 .…”
Section: The Upstream Regulatory Network Of the Hippo Signaling Pathwaymentioning
confidence: 99%
“…In addition, when the cells growing on the soft substrate do not have enough area to stretch, the mesenchymal stem cells will differentiate into adipocytes. The cell morphology becomes round, and YAP/TAZ is mainly distributed in the cytoplasm; on the contrary, mesenchymal stem cells differentiate into osteoblasts, and the cell morphology is flat, YAP/TAZ mainly located in the nucleus 47 , 49 .…”
Section: The Upstream Regulatory Network Of the Hippo Signaling Pathwaymentioning
confidence: 99%